Alkali/alkaline-earth metal intercalated g-C3N4 induced charge redistribution and optimized photocatalysis: status and challenges. (12th May 2021) - Cui, Wen; Chen, Peng; Chen, Lvcun; Li, Jieyuan; Zhou, Ying; Dong, Fan
Abstract: Limited by the intrinsic graphitic sp 2 -hybridized array of tri-s-triazine repeating units and inert stack of layers, the insertion of intercalant between layers of graphitic carbon nitride (CN) could be an effective way to strengthen the van der Waals force between adjoining layers and induce the charge redistribution in CN for the improvement of photocatalysis. This review summarizes the latest progress related to the design and construction of alkali/alkaline-earth metal intercalated CN, including (a) single alkali/alkaline-earth metal intercalated CN, (b) alkali/alkaline-earth metal and non-metallic species co-intercalated CN, (c) alkali/alkaline-earth metal intercalated and surface modification co-functionalized CN. The promotion mechanism of each classification will be critically discussed, namely alkali/alkaline-earth metal intercalated CN-induced charge redistribution facilitates the adsorption and activation of reactants, accelerates the separation efficiency of photogenerated carriers, and optimizes the reaction pathway. Also, the influence on band structure and optical property has been discussed with the intercalation of alkali/alkaline-earth metal. Finally, this mini-review highlights crucial issues that should be addressed in future research.